Development of Animated Video-Based Learning Media Using the Canva and Capcut Applications for Introductory Geography Material for Class X of SMA Negeri 12 Kupang City - Defriyani Ewalde Bria; Sukmawati; Maria Florent P. Jedo; Anastasia Regina Dero; Agnesia Elvira Molo (SOSEARCH : Social Science Educational Research, 2025)
This study aims to (1) Determine the level of feasibility of animated video-based learning media and (2) Analyze the effectiveness of animated video-based learning media created using the Canva and Capcut applications. This type of research is Research and Development (R&D) using the ADDIE development model. The process of developing animated video-based learning media starts from the analysis stage, followed by the design stage and enters the development stage, then the implementation stage and finally the evaluation stage. The validation results show that this media meets quality standards in terms of appearance, content, and effectiveness in delivering learning materials. The results of trials with students and teachers at SMAN 12 Kupang City show that the developed learning media is effective to use and students feel more motivated in learning and understanding the material through video media. It is recommended that teachers combine their teaching methods with video-based media to be more interactive. Further research is important to explore the extent to which the use of this media affects students in the long term.